IMEJ DESTINASI TERHADAP KEPUASAN DAN LOYALITAS WISATAWAN UNTUK BERKUNJUNG KEMBALI - tuti panghastuti; Anwani (Journal of Tourism Destination and Attraction, 2019)
This research will focus on the Tourist Destination Areas (DTW) of the museum considering the motives and tourist destinations are more unique, besides recreational motives there is an element of learning. The pattern of tourism in museum objects shows the fact that the number of tourist visits is relatively fixed from year to year. Investment in tourist destinations is very large, especially in artificial destinations. Visitors to tourist destinations, although satisfied, are less likely to visit again. So to foster loyalty it needs to be redefined. So this study aims to prove that high decisions do not necessarily form high loyalty. Therefore loyal tourists are not only willing to come back but are willing to promote the destinations visited either by word of mouth or recommend to others. This research uses a quantitative analysis method with an inferential approach. Theoretically, quantitative analysis in a study can be approached from two approaches, the first using descriptive statistics and the second using inferential statistics. Both types of statistics have different characteristics, both in terms of analytical techniques and the objectives that will result from the analysis. The output of this research is to develop the concept of strategy formulation for the marketing of tourist attraction objects especially museum destinations, and to develop the concept of marketing strategies in increasing tourist visits.